Teologi Saintifik-Budaya Hosah terkait Sakralitas Udara: Sains, Budaya Simalungun, dan Kristianitas dalam Trialog Konstruktif - Sipayung, Parulihan (Indonesian Journal of Theology, 2023)
This study aims to develop a constructive theology of hosah through an interdisciplinary approach. The research involves a scientific understanding of air, the Simalungun cultural concept of hosah, and Christian theology of the Holy Spirit. It employs a trialogical method consisting of two stages, namely, descriptive-comparative and normative-constructive. The first stage explains the concepts of air, hosah, and Spirit from scientific, cultural, and theological perspectives, respectively. The second stage focuses on constructing a theology of hosah. The results of this trialogue critically analyze, enrich, and revise these concepts. Overall, the study concludes that air is more than just a gaseous compound; it is a sacred altar of life.